Efficacy and Safety of a Novel Method of Insulated Intralesional Radiofrequency Ablation for Deep Dermal and Subcutaneous Lesions: A 3-Year Institutional Experience. Issue 5 (May 2018) - Subhadarshani, Sweta; Gupta, Vishal; Taneja, Neha; Yadav, Savita; Gupta, Somesh
Abstract : BACKGROUND: Although insulated intralesional radiofrequency ablation (IL-RFA) is being increasingly used in other specialties, not much information on its safety and efficacy in dermatology is available. OBJECTIVE: To describe our experience with insulated IL-RFA for various dermatological conditions. METHODS: This is a retrospective review of the patients who underwent IL-RFA in the past 3 years. Our technique involved creating a small window in the proximal end of plastic sheath of an intravenous cannula using a surgical blade, and then touching the RF probe to the cannula through the window to deliver the electric current. Information regarding diagnosis, number of sessions, adverse effects, and follow-up was recorded. Clinical improvement was assessed on a visual analog scale by the patient and 2 independent observers. RESULTS: Data on 19 patients with lymphangioma circumscriptum ( n = 9), venous or capillary-venous malformation ( n = 4), angiolymphoid hyperplasia with eosinophilia ( n = 3), arteriovenous malformation, hidradenitis suppurativa, and hypertrophic scar ( n = 1 each) was available. The mean number of IL-RFA sessions was 2.26 ± 1.61. The mean patient and physician global assessment scores were 7.6 ± 2.22 and 7.3 ± 2.42, respectively. Adverse effects were seen in 9 (47.4%) patients. All patients, except 1, had sustained improvement in the mean follow-up period of 11.4 ± 11.6 months. CONCLUSION: Insulated IL-RFA seems to be safe and effective in selectively targeting deep-seated cutaneous lesions. Abstract : Supplemental Digital Content is Available in the Text.